Distribution of heavy metals in the northern shrimp Pandalus borealis from the Oslofjord - Neelakantan, B. (1976)
Studies on the distribution of heavy metals like copper, cadmium, zinc, lead and mercury in deep sea prawns Pandalus borealis in the Oslofjord region showed that those collected from inner and middle fjord contained higher levels of heavy metals than those from the outer fjord. Their content in the edible portions, viz., tail muscle, was less compared to other organs. In terms of metal concentration copper and zinc are present in significant quantities in Pandalus borealis.